Self-reported perceptions of adults with diabetes regarding their care and health in the time of COVID-19 pandemic in a Swiss region: a cross-sectional study (Swiss Medical Weekly, 2024)
AIM: To assess the perceptions of adults with diabetes regarding their care and health during the COVID-19 pandemic in the canton of Vaud, Switzerland.METHODS: Cross-sectional data was analysed from the 2021 follow-up questionnaire of the CoDiab-VD survey, a cohort of adults living with diabetes in the canton of Vaud. Various aspects of diabetes care and issues relating to the COVID-19 pandemic were assessed. Descriptive analyses were conducted to detail access to care, self-management, and psychosocial burden during the pandemic. Regression analyses were then performed to explore the relationship between these domains and factors associated with COVID-19 outcomes.RESULTS: Respondents (n = 566; 79%) had a mean age of 70 years (range: 22–94), and most had type 2 diabetes (73%). The COVID-19 pandemic did not appear to have strongly affected their care. Indeed, access to diabetes care remained similar to before the pandemic: only 10% of respondents reported having diabetes-related care postponed or cancelled. While 16% experienced increased difficulty in managing physical activity, the majority were able to continue diabetes self-management, with minimal changes in glucose control. In terms of psychosocial burden, only 33% expressed high levels of worry about the pandemic.CONCLUSION: Diabetes self-management, glucose control, and access to diabetes care were not severely affected for the CoDiab-VD cohort during the COVID-19 pandemic. Despite some reported postponements in care and increased difficulty in physical activity management, the majority maintained their diabetes management practices with minimal impact on glucose control. Overall, psychosocial worry about the pandemic was relatively low, highlighting the resilience of individuals in managing their diabetes despite challenging circumstances.ClinicalTrials.gov number: NCT01902043